The Road Safety Literacy Strengthening Assistance For The Lentera Community (Orderly And Safe Literacy On The Highway) In Ponorogo Regency - Ida Yeni Rahmawati; Mohammad Bhanu Setyawan; Adi Fajaryanto Cobantoro; Susi Darihastining; Tri Wahyono; Siti Khoirul Bariyah (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The high number of traffic accidents, especially among students and novice drivers, indicates a low level of road safety literacy in the community. The LENTERA (Orderly and Safe Literacy on the Road) community in Ponorogo Regency was formed as an effort to build collective awareness of the importance of safe driving. This study aims to assist and strengthen the capacity of this community through structured interactive training. The method used in this activity is a participatory descriptive approach, with stages of socialization, training, and evaluation using pre-test and post-test instruments, as well as observation of participant involvement. The results showed a significant increase in participants' understanding of traffic safety principles, with an average pre-test score of 62.06 increasing to 85.12 in the post-test. Observations also showed an increase in participants' enthusiasm, analytical skills, and reflective awareness. The conclusion of this activity is that strengthening safety literacy through a community approach can encourage constructive and sustainable behavioral changes. It is recommended that this community-based training model be replicated in other regions, with cross-sector collaboration and the development of more contextual modules. Furthermore, the outreach materials presented should be based on factual data on frequent accidents and should provide insights into each incident, with the goal of reducing the number of road accidents, particularly among students. Materials supplemented with simulations of road traffic engineering provide knowledge that will be easier to understand in everyday practice and, of course, be more memorable.